PENGARUH KESEIMBANGAN DINAMIS TERHADAP PRESTASI LARI 400M - Saputra, Riski; Rubiyatno, Rubiyatno; Sastaman, Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to analyze the impact of dynamic balance on 400- meter running performance. The experimental method with a Pre-Test and Post-Test design was applied to 20 students from the Sports Coaching Education Program at Tanjungpura University. Participants underwent three types of treatments: zig-zag hopping with one foot, walking straight with a bottle on the head, and heel walking. The results showed a significant improvement in running speed after the treatments. The average running time before treatment was 1 minute and 21 seconds, which decreased to 53 seconds after the treatment. Statistical tests confirmed a significant effect of dynamic balance exercises on running performance. This study concludes that dynamic balance training effectively enhances speed, agility, and neuromuscular coordination, which are crucial for athletic performance. Additionally, incorporating these exercises in routine training may help prevent injuries by improving postural stability and movement efficiency. Coaches and athletes should prioritize balance exercises as a fundamental component of sports training to optimize endurance, strength, and overall performance in competitive running.